Postoperative delirium and changes in the blood–brain barrier, neuroinflammation, and cerebrospinal fluid lactate: a prospective cohort study. (August 2022) - Taylor, Jennifer; Parker, Margaret; Casey, Cameron P.; Tanabe, Sean; Kunkel, David; Rivera, Cameron; Zetterberg, Henrik; Blennow, Kaj; Pearce, Robert A.; Lennertz, Richard C.; Sanders, Robert D.
Abstract: Background: Case-control studies have associated delirium with blood–brain barrier (BBB) permeability. However, this approach cannot determine whether delirium is attributable to high pre-existing permeability or to perioperative changes. We tested whether perioperative changes in cerebrospinal fluid/plasma albumin ratio (CPAR) and plasma S100B were associated with delirium severity. Methods: Participants were recruited to two prospective cohort studies of non-intracranial surgery (NCT01980511, NCT03124303, and NCT02926417). Delirium severity was assessed using the Delirium Rating Scale-98. Delirium incidence was diagnosed with the 3D-Confusion Assessment Method (3D-CAM) or CAM-ICU (CAM for the ICU). CSF samples from 25 patients and plasma from 78 patients were analysed for albumin and S100B. We tested associations between change in CPAR ( n =11) and S100B ( n =61) and delirium, blood loss, CSF interleukin-6 (IL-6), and CSF lactate. Results: The perioperative increase in CPAR and S100B correlated with delirium severity (CPAR ρ =0.78, P =0.01; S100B ρ =0.41, P <0.001), delirium incidence (CPAR P =0.012; S100B P <0.001) and CSF IL-6 (CPAR ρ =0.66 P =0.04; S100B ρ =0.75, P =0.025). Linear mixed-effect analysis also showed that decreased levels of S100B predicted recovery from delirium symptoms ( P =0.001). Linear regression demonstrated that change in plasma S100B was independently associated with surgical risk, cardiovascular surgery, blood loss, and hypotension. Blood loss also correlated with CPAR ( ρ =0.64, P =0.04), S100B ( ρ =0.70, P <0.001), CSF lactate ( R =0.81, P =0.01), and peak delirium severity ( ρ =0.36, P =0.01). Conclusion: Postoperative delirium is associated with a breakdown in the BBB. This increased permeability is dynamic and associated with a neuroinflammatory and lactate response. Strategies to mitigate blood loss may protect the BBB.